2022
DOI: 10.1016/j.bonr.2021.101152
|View full text |Cite
|
Sign up to set email alerts
|

Low dose hydrophilic statins are the preferred agents for females at risk of osteoporosis

Abstract: Objectives The correlation between atherosclerosis and osteoporosis, independent of age, is clear. Multifactorial co-dependence between bone mineral density (BMD) and statin dose has been proposed. It is hypothesised that inhibition of the synthesis of cholesterol will also inhibit the synthesis of sex hormones and Vitamin D, negatively affecting BMD. This study aims to evaluate hydrophilic and non-hydrophilic statins effect on osteoporosis and analyse any possible superiority of one agent over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Anche se il ricorso alla terapia ipolipemizzante rappresenta la strategia d’elezione per la riduzione della morbilità e della mortalità cardiovascolari sia negli uomini che nelle donne ( 21 ), i risultati hanno mostrato un preponderante utilizzo di statine a bassa potenza nelle donne. Ciò potrebbe riflettere un’attitudine dei clinici a preferire per le donne terapie meno “aggressive” a causa dei noti effetti delle statine ad alte dosi sul rischio di osteoporosi, soprattutto dopo la menopausa ( 22 ). Vi sono ampie evidenze in letteratura a supporto dei nostri dati che indicano come le donne siano trattate in misura inferiore con statine, soprattutto ad alta potenza e abbiano maggiori tassi di non aderenza o interruzione e dunque minori probabilità di raggiungere gli obiettivi lipidici rispetto agli uomini ( 23 - 25 ).…”
Section: Discussioneunclassified
“…Anche se il ricorso alla terapia ipolipemizzante rappresenta la strategia d’elezione per la riduzione della morbilità e della mortalità cardiovascolari sia negli uomini che nelle donne ( 21 ), i risultati hanno mostrato un preponderante utilizzo di statine a bassa potenza nelle donne. Ciò potrebbe riflettere un’attitudine dei clinici a preferire per le donne terapie meno “aggressive” a causa dei noti effetti delle statine ad alte dosi sul rischio di osteoporosi, soprattutto dopo la menopausa ( 22 ). Vi sono ampie evidenze in letteratura a supporto dei nostri dati che indicano come le donne siano trattate in misura inferiore con statine, soprattutto ad alta potenza e abbiano maggiori tassi di non aderenza o interruzione e dunque minori probabilità di raggiungere gli obiettivi lipidici rispetto agli uomini ( 23 - 25 ).…”
Section: Discussioneunclassified
“…Therefore, the beneficial effect of statins on bone tissue metabolism results from their action through various mechanisms, as confirmed in numerous animal models of osteoporosis and mechanical bone damage [31][32][33][34][35]. Lipophilic statins, particularly simvastatin, lovastatin, and atorvastatin, appear to be the most effective in preventing osteoporosis and supporting the healing of bone fractures and defects [22,23,36].…”
Section: Statins-their Role In Bone Tissue Metabolismmentioning
confidence: 96%
“…It is important to note that only lipophilic statins can activate the promoter of this gene. Another suggested mechanism related to the primary target point of statins involves blocking HMG-CoA reductase, inhibiting the conversion of HMG-CoA to mevalonate, and indirectly limiting the biosynthesis of its derivatives, such as farnesyl pyrophosphate or geranylgeranyl pyrophosphate [22,[36][37][38][39]. These derivatives adversely affect bone tissue metabolism.…”
Section: Statins-their Role In Bone Tissue Metabolismmentioning
confidence: 99%
“…Cholesterol is a substance involved in the structural arrangement of the body and the regulation of cell function. As an important synthetic substance consisting of estrogen and vitamin D, cholesterol is involved in the regulation of bone metabolism ( 78 ). Previous studies have indicated that serum total cholesterol (TC) levels are negatively correlated with bone mineral density ( 71 , 79 ).…”
Section: Lipids and Osteoporosismentioning
confidence: 99%